Development of a sustainable Gynerium sagittatum panel for architectural interiors based on the ancestral Zenú knowledge of Colombia - Osorio, Pedro Arturo Martínez; Tuirán, Alexandra Castellanos; Da Cruz Landim, Paula [UNESP]; Barata, Tomás Queiroz Ferreira [UNESP] (Corporation Universidad de la Costa, CUC, 2023)
The results of a research are presented, in which substitute materials for wood were developed with a sustainable approach, applicable to the design of architectural interiors, based on the reinterpretation of artisanal techniques of the Zenú indigenous communities of Colombia. Following an experimental method, a compensated material made from strips of Gynerium sagittatum and PVA adhesive was developed. The material was characterized physically and mechanically in 2 series: 3 500 psi y 4 500 psi of cold pressure. The panels of series 1, presented a better performance in the tests, especially in the resistance tests, showing in the analyzes as a resistant material with a density range of 0.711 g/cm2; results for MOR 158.61 MPa and MOE 4912.72 MPa.
Desarrollo de panel sostenible de Gynerium sagittatum para interiores arquitectónicos a partir de los saberes ancestrales Zenú de Colombia
Keywords: architectural space; Gynerium sagittatum; indigenous knowledge; Plywood panels; sustainibility